Cutting Evaluation of HPWBM Drilling Mud Using CCI, CTR, and CCA Method at 17 ½ inch Hole in Directional Well G, Field S. - Gilbert Sunaryo; Abdul Hamid; Apriandi Rizkina Rangga Wastu (Journal of Earth Energy Science, Engineering, and Technology, 2022)
Quantitative analysis of cutting removal used in this study uses three methods, namely Cutting Carry Index, Cutting Transport Ratio, and Cutting Concentration in Annulus. This method is used to determine whether the composition of the mud used is maximal or not, starting from the maximum content of solids that can be carried in 1 gal to the viscosity and also the flow pattern of the fluid in order to successfully bring the cutting to the surface. Where these three methods have standardization to determine the cutting can be lifted, including for the cutting carry index method the value must be more than 1, for the cutting transport ratio the value must be greater than 50%, and for cutting concentration in annulus the value must be less than 5%. After analyzing the lifting using the three methods above, it can be seen the parameters in the successful removal of the cutting. These parameters include the physical properties of the fluid which includes the value of density, plastic viscosity, and also the yield point, while other parameters such as drill bit speed, mudflow velocity, cutting diameter are also important parameters in a successful borehole lifting. From the observations of this study, we can conclude that the use of mud in well G field S has been running optimally. The calculation of cutting lift has met the standardization limits. This study also carried out sensitivity analysis as a source of future literature, so that sensitivity analysis parameters can be used if you want to do a well development. This study shows an analysis of cutting lift on a 17.5 inch Route at a depth of 825ft - 2581ft, with an average drilling slope of 4 degrees per 100 ft.